The inhibition, reactivation and mechanism of VX-, sarin-, fluoro-VX and fluoro-sarin surrogates following their interaction with HuAChE and HuBuChE. (1st August 2018) - Chao, Chih-Kai; Balasubramanian, Narayanaganesh; Gerdes, John M.; Thompson, Charles M.
Abstract: In this study, the mechanisms of HuAChE and HuBChE inhibition by Me-P(O) (OPNP) (OR) [PNP =  p -nitrophenyl; R = CH2 CH3, CH2 CH2 F, OCH(CH3 )2, OCH(CH3 ) (CH2 F)] representing surrogates and fluoro-surrogates of VX and sarin were studied by in vitro kinetics and mass spectrometry. The in vitro measures showed that the VX- and fluoro-VX surrogates were relatively strong inhibitors of HuAChE and HuBChE (ki  ∼ 10 5 -10 6  M −1 min −1 ) and underwent spontaneous and 2-PAM-mediated reactivation within 30 min. The sarin surrogates were weaker inhibitors of HuAChE and HuBChE (ki  ∼ 10 4 -10 5  M −1 min −1 ), and in general did not undergo spontaneous reactivation, although HuAChE adducts were partially reactivatable at 18 h using 2-PAM. The mechanism of HuAChE and HuBChE inhibition by the surrogates was determined by Q-TOF and MALDI-TOF mass spectral analyses. The surrogate-adducted proteins were trypsin digested and the active site-containing peptide bearing the OP-modified serine identified by Q-TOF as triply- and quadruply-charged ions representing the respective increase in mass of the attached OP moiety. Correspondingly, monoisotopic ions of the tryptic peptides representing the mass increase of the OP-adducted peptide was identified by MALDI-TOF. The mass spectrometry analyses validated the identity of the OP moiety attached to HuAChE or HuBChE as MeP(O) (OR)-O-serine peptides (loss of the PNP leaving group) via mechanisms consistent with those found with chemical warfare agents. MALDI-TOF MS analyses of the VX-modified peptides versus time showed a steady reduction in adduct versus parent peptide (reactivation), whereas the sarin-surrogate-modified peptides remained largely intact over the course of the experiment (24 h). Overall, the presence of a fluorine atom on the surrogate modestly altered the rate constants of inhibition and reactivation, however, the mechanism of inhibition (ejection of PNP group) did not change. Graphical abstract: Image 1 Highlights: Fluoro-containing, p -nitrophenyl surrogates of VX and sarin inhibited HuAChE and HuBChE. VX-surrogates were more potent inhibitors than sarin-surrogates. Cholinesterase adducts formed from the VX-surrogates were reactivated. The mechanism of inhibition was elucidated by Q-TOF and MALDI-TOF mass spectrometry. The time course of VX-modified cholinesterase reactivation was monitored using MALDI-TOF MS.